2017
DOI: 10.1080/10717544.2016.1230902
|View full text |Cite
|
Sign up to set email alerts
|

In vivo synergistic anti-tumor effect of paclitaxel nanoparticles combined with radiotherapy on human cervical carcinoma

Abstract: In this study, our purpose was to explore the synergistic anti-tumor effect and mechanism of paclitaxel nanoparticles (PTX-NPs) combined with radiotherapy (RT) on human cervical carcinoma (HeLa). PTX-NPs were prepared by a solid dispersion method using methoxy poly(ethylene glycol)-poly(e-caprolactone) (MPEG-PCL), which combined with RT exerted a potent and high efficient effect against cervical cancer. In vivo antitumor activity of PTX-NPs combined with RT, was estimated using nude mice carrying Hela cell xen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
(64 reference statements)
0
26
0
Order By: Relevance
“…In our previous study, we demonstrated that MPEG-PCL nanoparticles were outstanding carriers for hydrophobic drugs in virtue of the hydrophilic Time (days) Body weight (g) 28 34 PEG segment being introduced into PCL backbones. [25][26][27][28] Therefore, in our study, MPEG-PCL was used as a carrier to prepare Ola-NPs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, we demonstrated that MPEG-PCL nanoparticles were outstanding carriers for hydrophobic drugs in virtue of the hydrophilic Time (days) Body weight (g) 28 34 PEG segment being introduced into PCL backbones. [25][26][27][28] Therefore, in our study, MPEG-PCL was used as a carrier to prepare Ola-NPs.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] These nanoparticles had stable particle size with a higher DL when compared with other methods reported in recent studies. 25,32,33 The lyophilized nanoparticles were relatively narrowly distributed and could be stably dissolved in water to achieve the requirements for intravenous injection. Recent studies have shown that the importance of nanoparticle size will greatly affect the metabolism of nanoparticles: ,200 nm of nanoparticles will result in a longer blood circulation time, favorable stability, lower cytotoxicity, and greater absorptive capacity due to EPR effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cervical cancer is the second most common type of cancer in females worldwide, and is associated with local invasion and recurrent tumors (Yu et al, 2017). Several studies have demonstrated that local treatment of cervical cancer may reduce parametrial infiltration and destroy micrometastases, thereby decreasing relapse and metastasis (Thomas, 1999(Thomas, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…In aqueous media, the copolymer may form core-shell nanostructures with an inner hydrophobic core and outer hydrophilic shell due to high solubility. [23][24][25] Encapsulation of hydrophobic drugs into polymeric nanoparticles may present a hydrophilic stabilizing interface that can prolong the circulation time in vivo and may further enhance the cellular uptake. More importantly, due to enhanced permeability and retention (EPR) effects, polymeric nanoparticles may improve the anti-tumor effects by passively targeting tumors.…”
Section: Introductionmentioning
confidence: 99%